IMPROVING READING COMPREHENSION ON RECOUNT TEXT BY USING AUTHENTIC MATERIAL - Yeni Mustika (ELTR Journal, 2020)
The research was aimed to improve students’ reading comprehension on recount text by using authentic material to Class IIS 2 students of Year-10 in SMAN 1 Mempawah, membership of 33 students. This research was a Classroom Action Research with two cycles. Each cycle consisted of planning, acting, observing, and reflecting. Field notes, observation checklist, video recording, and individual tests were used as the tools to collect the data. Qualitative and quantitative analyses were used to analyze the data. The finding showed that there was a significant improvement from cycle to cycle. Through authentic material, the students were able to improve their reading comprehension well. It helped the students to learn with the real model and found an interesting way in the learning process. The researcher focused on reading comprehension of recount text by using authentic printed materials in kinds of newspapers. It was very appropriate, effective, and helpful to be used by the teachers in teaching reading comprehension on recount text.